Biocontrole de murcha bacteriana em tomateiro por meio da incorporação de resíduos orgânicos ao solo - Nascimento, Alexsandra Sousa (2005)
The bacterial wilt, caused by Ralstonia solanacearum (Smith) Yabuuchi, is an important disease of tomatoes plant in Maranhão, its control has not been efficient to reduce of the damages and the economic losses caused by attack of its causal agent. The objective of the present research was to evaluate the action of the organics residues: cassava (Manihot esculenta Crantz), Indian neen (Azadirachta indica Juss.) and citronela (Cymbopogon nardus L) on the biocontrol of the bacterial wilt of tomatoes plants. The organics residues were incorporated in the soil using following dosages: 0, 20, 40, 60, 80 and 100 g/L-1, at five differents periods: 0, 15, 30, 45 and 60 days. The experiments were conducted in greenhouses of Agronomical Center Biotechnology of the Universidade Estadual do Maranhão - UEMA. Eight isolates of R. solanacearum, biovars 1 and 3, from different geographics regions of the country were tested. The evaluation of the aggressiveness of the isolates allowed the election of the isolate 206, biovar 1, collected in Goiânia (GO). The prepare of the substratum that was used involved the mixture of soil steril with dry, triturated and milled out residues, in its respective preselected dosages. This one was placed in plots with capacity for 1 L and kept grennhouse in the periods of incorporation preselected. Seedlings were prepared in trays and transplanted for the plots contend the substratum. The inoculations methods consisted of the cut of the roots system with scissor followed by immersion of the roots in bacterial suspension (108 ufc/mL). The evaluations were made from the fifth to the tenth day after the inoculation, considering the number of healthy, wilt or died seedlings. The experimental design was a blocks randomized, with six replications, being the experimental parcel consisted by six plots, with one plant for each plot. Results showed the efficiency of the incorporation of the residues in the soil, on the disease development. The cassava scrap was more efficient on 30 days at the 20 g/L-1 dosage of. Indian neem presented better results on 30, 45 and 60 days of incorporation the dosages 100 and 80 g/L-1, while citronela was efficient in all dosages and periods of incorporation.